Rancang Bangun Prototype Dekanter dengan Sistem Elektrokoagulasi untuk Proses Pemisahan Gliserol dalam Crude Biodiesel - Mandalini, Larisa; Stivano, Diva; Nirmala, Dyah; Akbar, Addin (Jurnal Serambi Engineering, 2026)
This study aims to examine the effectiveness of an electrocoagulation (EC) system in biodiesel purification using a combination of iron rod and aluminum disk electrodes in a cone-bottom decanter, compared to conventional gravity decantation. The apparatus design includes a 4-liter working volume, 1 cm electrode spacing, and operation at 15 V AC for 1 hour. The results indicate that EC significantly accelerates glycerol separation, requiring only 1 hour compared to gravity decantation, which takes over 24 hours. The glycerol separation efficiency with EC reached 98.49%, higher than that of gravity decantation (97.70%). Biodiesel produced via EC yielded a total glycerol content of 0.19%, meeting the SNI standards (< 0.24%), whereas gravity decantation resulted in 0.29%. Other parameters, such as density (0.86 g/mL), viscosity (5.8 cSt), water content (0.008%), and %FAME (98.36%), also complied with the standards. In conclusion, the electrocoagulation system with a stacked disk electrode configuration is more effective in accelerating separation and improving biodiesel quality.